Postharvest losses and mitigating technologies: evidence from Upper East Region of Ghana. (2021) - Sugri, Issah; Abubakari, Mutari; Owusu, Robert Kwasi; Bidzakin, John Kamburi
Abstract: Post-harvest losses (PHL) have been identified as a crucial challenge to achieving food and nutrition security in sub-Saharan Africa. Access to reliable data and standardized methods of estimating PHL are a twin barrier to developing long term mitigation options and policies to reduce PHL. This study assessed PHL in 6 districts of the Upper East Region of Ghana to facilitate planning and dissemination of mitigating strategies. The second part involved participatory evaluation of improved storage technologies to reduce PHL in two vulnerable crops (maize and cowpea). Overall, farmers' declared PHL were higher across the crops compared to laboratory measurement. Crops recording higher PHL were in order of cowpea (17.3%), Bambara nut (11.5%), groundnut (8.9%) and maize (8.2%). By disseminating appropriate technologies to farmers, PHL were reduced to 3.1% from 36.7% in maize and 6.4% from 77.8% in cowpea during 12 months of storage. In spite of the high PHL, the respondents showed low technical and resource capabilities to minimize losses. Other factors contributing to PHL were the small-scale nature of production, and high cost of improved techniques tailored for same smallholders. Although the improved storage methods were associated with high variable costs, all the treatments showed positive stream of discounted net benefits .